2020
DOI: 10.3389/fnut.2020.595964
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds With Antibacterial Activity Against Cronobacter spp. in Powdered Infant Formula: A Review

Abstract: Bacteria from the genus Cronobacter are opportunistic foodborne pathogens capable of causing severe infections in neonates, the elderly and immunocompromised adults. The majority of neonatal infections have been linked epidemiologically to dehydrated powdered infant formulas (PIFs), the majority of which are manufactured using processes that do not ensure commercial sterility. Unfortunately, the osmotolerance, desiccation resistance, mild thermotolerance and wide-ranging minimum, optimum and maximum growth tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 157 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Therefore, attention has been increased to use various natural additives, such as sweeteners, coloring, antioxidants and antimicrobials agents obtained from microorganisms, plants, and animal ( 7 , 8 ). Various natural antimicrobial agents, such as essential oils and herbal extract, bacteriocin, and antimicrobial enzymes have been identified ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attention has been increased to use various natural additives, such as sweeteners, coloring, antioxidants and antimicrobials agents obtained from microorganisms, plants, and animal ( 7 , 8 ). Various natural antimicrobial agents, such as essential oils and herbal extract, bacteriocin, and antimicrobial enzymes have been identified ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamon is a traditional spice, which is widely used around the world [ 7 ]. It has also been used since ancient times as a food preservative by acting against foodborne pathogens and spoilage bacteria [ 8 ]. Cinnamon extract components have demonstrated a range of medical properties, cinnamic acid possesses antibacterial activity based on directed self-assembly [ 9 ]; procyanidin C1 acts as a potential insulin sensitizer that targets adipocytes [ 10 ]; trans-cinnamaldehyde (TCA) mitigates intestinal inflammation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a common lipid molecule in biological samples [ 51 ]. It has been reported that certain individuals may experience allergies with increased 2,3-dihydroxypropyl octanoate [ 52 ]. Interestingly, it is reported that alloys containing molybdenum may induce allergies such as eczema and impaired wound [ 53 ], suggesting that the up-regulation of 2,3-dihydroxypropyl octanoate caused by molybdate exposure in this study might promote allergies in mice.…”
Section: Discussionmentioning
confidence: 99%